Structure and Regulation of the Electricity Networks in Pakistan (The Pakistan Development Review, 2014)
This paper studies the electricity industry network in Pakistan, particularly in the context of structural and regulatory reforms started in the 1990s. Published reports by the regulator show that the reforms process is not going anywhere even after two decades and the industry is performing poorly [NEPRA1 (2010)]. The market is not clearing as load demand is higher than total system supply, particularly during the summer season.2 There is no electricity, due to load shedding, for long hours in major parts of country served by the distribution networks during the hot and long summer period. An effort is made here to document the basic facts of industry in an orderly manner and to draw major lessons from the failure of the reforms process and poor functioning of the electricity market. The focus will be on the electricity supply chain networks and issues in the regulation of the electricity industry. The restructuring of the natural monopoly components of industry will be discussed in detail. The electricity industry in Pakistan is quite under researched [Pakistan (2013)], the main source of industry knowledge is based on government publications. According to available research [NEPRA (2011), Malik (2007)], the rich information provided in policy documents and regulatory reports has not been analysed in detail. Therefore, documenting basic industry facts and related issues in this paper is a contribution to the existing literature and will be useful for future policy reforms.